Impact of inclusion of graphene oxide nanosheets on polypropylene thermal characteristics - Sabet, M. (Springer Science and Business Media Deutschland GmbH, 2020)
Thermal steadiness and flame-resistant characteristics of PP/GO nanocomposites were explored. Inclusion of graphene oxide nanosheets (GOs) increased thermal steadiness of the nanocomposites by at least 50Â Â°C through nano-confinement of PP connections and restriction of release of gaseous molecules during degradation. Pyrolysis showed that process of the degradation of PP was not changed in the presence of nanofillers and alkenes consisting of carbon particles that were deterioration products. With addition of GOs to PP, cone calorimetry experiments exposed a substantial deviation in ignition under irradiation. In addition, inclusion of GOs reduced PP's rate of combustion owing to the creation of a carbon shielding sheet acting as the heat and mass transfer barrier. Uniformly dispersed GOs shifted the decomposing onset temperature (Tonset) of PP to around 40Â Â°C higher which induced a great melt flow rate in the composites and dramatically changed their fire behavior. Delayed dripping resulted in considerably enhanced heat absorptionÂ andÂ reduced time for ignition. As a result of development of a shielding film in combustion, under flaming conditions,Â the highest thermal discharge level of 78 was accomplished. The most prominent features that made PPÂ to prefer carbon nanoparticles were demonstrated by the well-exfoliated GO nanosheets in the PP matrix which was evidenced by TEM images. Findings of TGA indicated that the GO's addition enhanced the thermal steadinessÂ and PP's char yields. The nanocomposites of PP/GO 5.0 wt attained UL-94 with a grade of no dripping and grade V-1. Cone calorimeter test results showed that the PP's burning performance, peak heat release rate (PHRR) and average specific extinction area decreased noticeably when the GOs' combination effects was intervened. PHRR showed a decrease of 46Â compared to the neat PP for the PP/GO 5.0 wt nanocomposite. This role offered a new modified approach to enhance the GO's flame-resistant effectiveness. Â© 2020, Iran Polymer and Petrochemical Institute.